Precipitation of Clinical Infections in Chickens by Infectious Bursal Disease Virus Preserved under Different Storage Temperatures - Idachaba, S.E.; Nwosuh, C.; Aba-Adulugba, E.P.; Fasina, F.O. (International Journal of Poultry Science, 2009)
Biological activities and precipitation of clinical infection potentials of Infectious Bursal Disease Virus (IBDV) stored under different storage conditions were assessed in cockerel chicks. Infective bursae were stored for between 10-20 months at different storage temperature (+4oC, -20oC and -196oC), homogenized and used to challenge IBD-antibody-naïve chickens at 21 days of age. Clinical infections were precipitated in varying degrees. The sample stored at -196oC produced the most marked effect (signs, symptoms and deaths) in susceptible chickens and had an index score of 8.700; followed by the bursae tissue stored at -20oC with an index score of 5.167. The tissue stored at +4oC produced barely insignificant symptomatic/clinical effects in the chickens. This affirms that biological activities of infectious organisms like IBDV is best maintained at deep freezing or ultra low temperature.